2003
DOI: 10.1177/014556130308200718
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Pseudotumor of the Trachea

Abstract: Inflammatory pseudotumor" is a broad descriptive term used to describe a localized collection of inflammatory and fibroblastic cells. It is an uncommon lesion that can mimic a tumor when it is located intraluminally in the trachea or bronchi. Because an inflammatorypseudo tumor has an abundance of polyclonal plasma cells, its etiology (postinflammatory vs immunologic) is still being debated. We report a new case ofinflammatorypseudotumor that arose in the trachea of a 20-year-old man. We also review the histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Inflammatory pseudotumors do not present an identifiable common cause, but some authors believe that any inflammatory stimulus can trigger it. [ 1 7 8 ] It has been postulated that they may be the result of a postinflammatory repair process, a metabolic disorder, or an antigen–antibody interaction with an agent that was no longer identified in aspiration or biopsy material. [ 8 ] In the present study, it was not possible to observe a triggering process for its development, confirming an uncertain etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory pseudotumors do not present an identifiable common cause, but some authors believe that any inflammatory stimulus can trigger it. [ 1 7 8 ] It has been postulated that they may be the result of a postinflammatory repair process, a metabolic disorder, or an antigen–antibody interaction with an agent that was no longer identified in aspiration or biopsy material. [ 8 ] In the present study, it was not possible to observe a triggering process for its development, confirming an uncertain etiology.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In some patients, laboratory findings are normal; in others, there might be an elevated erythrocyte sedimentation rate and C-reactive protein level and sometimes a high white blood cell count. 12 However, none of the published reports on inflam matory pseudotumor have mentioned any presence of positive tumor markers. 6…”
Section: Discussionmentioning
confidence: 99%
“…33 Cough, fever, and recurrent respiratory tract infections are the most frequently presenting symptoms, whereas hemoptysis, chest pain, mediastinal mass, dyspnea, stridor, wheezing, dysphagia, pleuritic pain, right upper quadrant pain, epigastric pain, and weight loss occur less frequently. 6,8,15,39 We reviewed 61 cases of endobronchial inflammatory pseudotumors in children 28,37,[40][41][42][43][44][45][46][47][48][49][50][51] and found that the most presenting symptoms were pneumonia, cough, asymptomatic presentation, and chest pain ( Table 1). 38 Intratracheal and endobronchial lesions can manifest with obstructive pulmonary symptoms and are often misdiagnosed as bronchial asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The true incidence of inflammatory pseudotumor is difficult to estimate because of the various synonyms used. 8,9,11,12 The standard treatment of inflammatory pseudotumors is surgical removal with high risk of recurrence when incompletely excised. 8,9,11,12 The standard treatment of inflammatory pseudotumors is surgical removal with high risk of recurrence when incompletely excised.…”
mentioning
confidence: 99%